2021
DOI: 10.3899/jrheum.210724
|View full text |Cite
|
Sign up to set email alerts
|

Case of Giant Cell Arteritis After SARS-CoV-2 Vaccination: A Particular Phenotype?

Abstract: We read with great interest the article by Mehta et al about the similarities and discriminators between giant cell arteritis (GCA) and the coronavirus disease 2019 (COVID-19).1 Viruses have been suspected to be implicated in the pathogenesis of GCA, especially the varicella zoster virus,2 but a clear association has not been confirmed.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…It has been suggested that portal infiltration with eosinophils correlates with drug-induced liver injury, including vaccines (i.e., Moderna mRNA-1273 and AstraZeneca ChAdOx1 nCoV-19 vaccines) [ 8 , 27 , 28 ]. This could partially explain the existence of hepatitis following vaccination without positivity for liver-associated autoantibodies ( Table 1 ) [ 8 , 10 , 12 , 13 , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that portal infiltration with eosinophils correlates with drug-induced liver injury, including vaccines (i.e., Moderna mRNA-1273 and AstraZeneca ChAdOx1 nCoV-19 vaccines) [ 8 , 27 , 28 ]. This could partially explain the existence of hepatitis following vaccination without positivity for liver-associated autoantibodies ( Table 1 ) [ 8 , 10 , 12 , 13 , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] ].…”
Section: Discussionmentioning
confidence: 99%
“… Aldolase raise (10,3 U/L NV < 7.6) ANAS 1:160, borderline positivity Anti-Pm/scl-75 antibodies Electromyography: moderate severity subacute myositis without muscle damage and polyneuropathy. Conticini et al [ 44 ] Relapse of microscopic polyangiitis Pfizer- BioNTech mRNA vaccine Few days after 1 dose Arterial blood pO2 48 mm Hg) CRP 3.7 mg/dL, creatinine 1.55 mg/dL Negative autoimmunity blood tests High‐resolution computed tomography: diffuse “ground‐glass” opacities with superimposed septal thickening and subpleural consolidations Sauret et al [ 13 ] Giant Cell Arteritis AstraZeneca ChAdOx1 nCoV-19 vaccine Few days after 1 dose GGT 112 U/L, ALP 40 U/L Authors did not performed autoantibodies Ishay et al [ 10 ] Pfizer- BioNTech mRNA vaccine Case 1: 3 days after 1 dose Case 1: Negative ANAs, RF, and anti-CCP antibodies Case 1: Symmetric polyarthritis Case 2: 10 days after 1 dose Case 2: No autoantibodies Case 2: Exacerbation of Beçet disease Case 3: 1 day after 1 dose Case 3: No autoantibodies Case 3: Pericarditis Case 4: 3 days after 1 dose Case 4: No autoantibodies Case 4: Termporal arteritis like disease Case 5: Few hours after 1 dose Case 5: No autoantibodies Case 5: <...>…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sauret et al [35] also reported the case of a patient who developed GCA following SARS-CoV-2 vaccination. The patient was positive for HLA-DR4, which made the author hypothesize that HLA could play a role in the occurrence of post-vaccinal GCA.…”
Section: Severe Acute Respiratory Syndrome Coronavirus-2 (Sars-cov-2)mentioning
confidence: 99%
“…Other differentials of headache with pleocytosis not considered include reversible, cerebral vasoconstriction syndrome (RCVS) [ 6 7 ], subarachnoid bleeding, and cerebral vasculitis [ 8 ]. Since RCVS has been previously reported as a complication of SARS-CoV-2 vaccinations [ 7 ], and since it usually responds favourably to nimodipine, it is crucial to exclude this differential upon computed tomography angiography [ 6 ].…”
mentioning
confidence: 99%